2020
DOI: 10.1111/jgs.16623
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐SAFER: Deprescribing Guidance for Hydroxychloroquine Drug Interactions in Older Adults

Abstract: BACKGROUND/OBJECTIVES: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes high morbidity and mortality in older adults with chronic illnesses. Several trials are currently underway evaluating the antimalarial drug hydroxychloroquine as a potential treatment for acute infection. However, polypharmacy predisposes patients to increased risk of drug-drug interactions with hydroxychloroquine and may render many in this population ineligible to participate in trials. We aimed to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
0
29
0
3
Order By: Relevance
“…It is possible that hydroxychloroquine is more effective in populations at higher risk for complications, such as older persons in long-term care facilities (23). Performing randomized trials in long-term care facilities could test whether hydroxychloroquine can reduce hospitalizations; however, the risk for medication adverse effects and drug-drug interactions will also be higher (24).…”
Section: Original Researchmentioning
confidence: 99%
“…It is possible that hydroxychloroquine is more effective in populations at higher risk for complications, such as older persons in long-term care facilities (23). Performing randomized trials in long-term care facilities could test whether hydroxychloroquine can reduce hospitalizations; however, the risk for medication adverse effects and drug-drug interactions will also be higher (24).…”
Section: Original Researchmentioning
confidence: 99%
“…The COVID-Safer study exploited a similar strategy by using retrospective data from hospitalized older adults with polypharmacy included in the primary MedSafer study, and they theoretically exposed this patient population cohort to a treatment of HCQ (5 days at a minimum dose of 600 mg daily) [50]. They identified possible drug-drug interactions as well as potential harmful outcomes such as increased toxicity of HCQ, risk of QTc prolongation or malignant cardiac arrhythmia, or risk of other adverse drug events requiring closer monitoring during therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in northern Italy COVID-19 patients experienced significant elevated plasma concentrations of direct oral anti-coagulants while on medications used in the course of COVID-19 [ 10 ]. Unfortunately, with the exception of hydroxychloroquine and QTc-time prolongation due to co-administration of other drugs, the issue of potential harmful DDI in COVID-19 comorbid patients seems to be of minor attention with a limited number of published studies currently available [ [11] , [12] , [13] , [14] , [15] ]. Also, of a public health concern is the use of self-medication being potentially harmful or without evidence of clinical benefit taking place particularly in low- and middle-income countries with restricted access to quality healthcare and where drug dispensing is less controlled in the communities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%